Estrategias para el control de la congestión en el servicio aBR de ATM - Becerra Forigua, Gloria Esperanza; Jerez, Carolina; Plazas, Víctor Manuel (Ingeniería, 1999)
Congestion is a problem for final users of network services, this fact is a good justification to work in congestion control mechanism. This article is a short description of congestion and it presents the goals to achieve in designing and implementation of network congestion control, especially in ATM ABR service. Finally and overview of alternatives is presented, and some conclusions are presented about our work.